EVALUASI WAKTU KERJA EFEKTIF ALAT GALI MUAT EXCAVATOR HITACHI ZX-350 H DAN KOMATSU PC 200 DALAM RANGKA MENCAPAI TARGET 80.000 TON PADA PENAMBANGAN BATU ANDESIT DI PT. KOTO ALAM SEJAHTERA KABUPATEN 50 KOTA, PROVINSI SUMATERA BARAT - Rahmahtul Fadlillah; Adree Octova (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. In andesite mining, PT. Koto Alam Sejahtera uses a series of work, namely using a digging and loading equipment to move material from the loading point to the dump hopper. Based on the results of field observations, the authors found that the actual data obtained were not in accordance with the target set by the company that the production target was not achieved due to several factors, including due to lost time and delay of the digging equipment, planned and not achieved production targets. As it should be, productive work time is not optimal. There are still frequent inconsistencies in work between the digging and loading equipment, where the digging tool often waits. This is due to the low actualization of working time against the productive time of the loading and transportation means, which causes a decrease in the efficiency of the work of the tools caused by various kinds of obstacles in the field that can actually be avoided.Keywords: excavator, Production, Effective Working Hours, Evaluation